Frontiers of Engineering: Reports on Leading Edge Engineering From the 1998 NAE Symposium on Frontiers of Engineering - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 1999)
Keywords: Engineering and Technology

Frontiers of Engineering: Reports on Leading Edge Engineering from the 1997 NAE Symposium on Frontiers of Engineering - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 1998)
Space may have been called the final frontier, but there are new frontiers to discover every day, and engineers are the ones exploring them. Through groundbreaking research and new technologies, engineers are able to go beyond traditional boundaries to do things that would have been all but impossible just a few years ago. This book, the most recent in a series of publications, describes new and emerging technologies and explains how they were developed and the benefits they will bring. It also offers highlights of the pioneering research and technological work being done by some of the country's emerging leaders in engineering. Topics include biomechanics, sensors and control for manufacturing processes, safety and security issues, decisionmaking tools for design and manufacturing, and intelligent transportation systems.
Keywords: Engineering and Technology

Understanding the Educational and Career Pathways of Engineers - National Academy of Engineering (The National Academies Press, 2018)
Engineering skills and knowledge are foundational to technological innovation and development that drive long-term economic growth and help solve societal challenges. Therefore, to ensure national competitiveness and quality of life it is important to understand and to continuously adapt and improve the educational and career pathways of engineers in the United States. To gather this understanding it is necessary to study the people with the engineering skills and knowledge as well as the evolving system of institutions, policies, markets, people, and other resources that together prepare, deploy, and replenish the nation's engineering workforce. This report explores the characteristics and career choices of engineering graduates, particularly those with a BS or MS degree, who constitute the vast majority of degreed engineers, as well as the characteristics of those with non-engineering degrees who are employed as engineers in the United States. It provides insight into their educational and career pathways and related decision making, the forces that influence their decisions, and the implications for major elements of engineering education-to-workforce pathways.
Keywords: Engineering and Technology

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2018 Symposium - National Academy of Engineering (The National Academies Press, 2019)
This volume presents papers on the topics covered at the National Academy of Engineering's 2018 US Frontiers of Engineering Symposium. Every year the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and innovations in selected areas. The 2018 symposium was held September 5-7 and hosted by MIT Lincoln Laboratory in Lexington, Massachusetts. The intent of this book is to convey the excitement of this unique meeting and to highlight innovative developments in engineering research and technical work.
Keywords: Engineering and Technology

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2017 Symposium - National Academy of Engineering (The National Academies Press, 2018)
This volume presents papers on the topics covered at the National Academy of Engineering's 2017 US Frontiers of Engineering Symposium. Every year the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and innovations in selected areas. The 2017 symposium was held September 25-27 at the United Technologies Research Center in East Hartford, Connecticut. The intent of this book is to convey the excitement of this unique meeting and to highlight innovative developments in engineering research and technical work.
Keywords: Engineering and Technology

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2016 Symposium - National Academy of Engineering (The National Academies Press, 2017)
This volume presents papers on the topics covered at the National Academy of Engineering's 2016 US Frontiers of Engineering Symposium. Every year the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and innovations in selected areas. The 2016 symposium was held September 19-21 at the Arnold and Mabel Beckman Center in Irvine, California. The intent of this book is to convey the excitement of this unique meeting and to highlight innovative developments in engineering research and technical work.
Keywords: Engineering and Technology

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2019 Symposium - National Academy of Engineering (The National Academies Press, 2020)
This volume of Frontiers of Engineering presents papers on the topics covered at the National Academy of Engineering’s 2019 US Frontiers of Engineering Symposium, hosted by Boeing in North Charleston, South Carolina, September 25-27. At the annual 2 1/2-day event, 100 of this country's best and brightest early-career engineers - from academia, industry, and government and a variety of engineering disciplines - learn from their peers about pioneering work in different areas of engineering. Frontiers of Engineering conveys the excitement of this unique meeting and highlights innovative developments in engineering research and technical work.
Keywords: Engineering and Technology

Autonomy on Land and Sea and in the Air and Space: Proceedings of a Forum - National Academy of Engineering (The National Academies Press, 2018)
Autonomy is multidisciplinary, multicultural, and global in its development and applications. Autonomous vehicles rely on communications, artificial intelligence, sensors, virtual and enhanced reality, big data, security, and many other technologies. Each year the annual meeting of the National Academy of Engineering highlights an engineering theme that is quickly developing in the world. The theme of the 2017 meeting was autonomy on land and sea and in the air and space. This publication summarizes the presentations and discussions from the meeting.
Keywords: Engineering and Technology

The Climate Change Educational Partnership: Climate Change, Engineered Systems, and Society: A Report of Three Workshops - National Academy of Engineering (The National Academies Press, 2014)
Societies develop engineered systems to address or mediate climate-related problems, such as drought, sea-level rise or wildfire control; the mediation involves public trust, public engagement, and governance. In these efforts, societies also decide - intentionally or implicitly - questions of justice and sustainability, such as what areas will receive mediation measures, what types of measures will be used, and what levels and kinds of local impacts are tolerated. In September 2010, the Center for Engineering, Ethics, and Society at the National Academy of Engineering began working with four other partners on a Climate Change Educational Partnership Phase I planning grant from the National Science Foundation. The project focused on defining and characterizing the societal and pedagogical challenges posed by the interactions of climate change, engineered systems and society, and identifying the educational efforts that a network could use to enable engineers, teachers, students, policymakers, and the public to meet the challenges. The project also aimed to build awareness of the complexities among a diverse set of communities affected by climate change and engineered systems and to engage the communities in addressing these challenges. The Climate Change Educational Partnership is the summary of three workshops convened over the course of the grant on the interactions of climate change with engineered systems in society and the educational efforts needed to address them. The first workshop provided the partners with an introduction to the varied social and technical dimensions found in the relationships among climate, engineered systems, and society. The second workshop built on the common language developed in the first. It allowed the partners to expand involvement in the project to include representatives from community and tribal colleges, professional societies and business. It examined the opportunities and challenges for formal and informal education, particularly in engineering classrooms and science museums, to prepare students and citizens to address these issues. The third workshop allowed the partners to broaden further the discussion and the audience. It solicited participation from government officials, Native American tribal representatives, professional society leaders, as well as educators, artists, scientists, and engineers who are developing programs that can manage change and educate students and citizens in ways that foster their leadership skills. The Climate Change Educational Partnership will be a useful resource to engineers, educators, corporate leaders, local and regional officials, members of professional societies, and others in their efforts to understand and address the challenges of climate change and its societal impacts.
Keywords: Engineering and Technology

Messaging for Engineering: From Research to Action - National Academy of Engineering (The National Academies Press, 2013)
For those in the broad engineering community--those who employ, work with, and/or educate engineers, and engineers themselves--there is no need to explain the importance and value of engineering. They understand that engineers help make the world a better place for all, that they regularly grapple with important societal and environmental issues, and that the engineering process is every bit as creative as composing a symphony or crafting a piece of art. But the situation outside the engineering community is quite different. Studies have shown that most K-12 students and teachers have a limited appreciation of all the ways that engineering makes their lives better and, furthermore, that they have little understanding of what engineers do or of the opportunities that an engineering education offers. Messaging for Engineering supports efforts by the engineering community to communicate more effectively about the profession and those who practice it. This report builds on the 2008 NAE publication, Changing the Conversation: Messages for Improving Public Understanding of Engineering (CTC), which presented the results of a research-based effort to develop and test new, more effective messages about engineering. The new messages cast engineering as inherently creative and concerned with human welfare, as well as an emotionally satisfying calling. This report summarizes progress in implementing the CTC messages, but also recognizes that there is potential to galvanize additional action and thus suggests specific steps for major players in the engineering community to continue and build on progress to date. Many of the report's recommendations resulted from discussion at a December 2010 committee workshop that involved several dozen high-level decision makers representing key stakeholder groups in the engineering community.
Keywords: Engineering and Technology

Emerging Technologies and Ethical Issues in Engineering: Papers from a Workshop - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2004)
Engineers and ethicists participated in a workshop to discuss the responsible development of new technologies. Presenters examined four areas of engineering--sustainability, nanotechnology, neurotechnology, and energy--in terms of the ethical issues they present to engineers in particular and society as a whole. Approaches to ethical issues include: analyzing the factual, conceptual, application, and moral aspects of an issue; evaluating the risks and responsibilities of a particular course of action; and using theories of ethics or codes of ethics developed by engineering societies as a basis for decision making. Ethics can be built into the education of engineering students and professionals, either as an aspect of courses already being taught or as a component of engineering projects to be examined along with research findings. Engineering practice workshops can also be effective, particularly when they include discussions with experienced engineers. This volume includes papers on all of these topics by experts in many fields. The consensus among workshop participants is that material on ethics should be an ongoing part of engineering education and engineering practice.
Keywords: Engineering and Technology

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2014 Symposium - National Academy of Engineering (The National Academies Press, 2015)
This volume presents papers on the topics covered at the National Academy of Engineering's 2014 US Frontiers of Engineering Symposium. Every year the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and innovations in selected areas. The 2014 symposium was held September 11-13 at the National Academies Beckman Center in Irvine California. The topics covered at the 2014 symposium were: co-robotics, battery materials, technologies for the heart, and shale gas and oil. The intent of this book is to convey the excitement of this unique meeting and to highlight innovative developments in engineering research and technical work.
Keywords: Engineering and Technology

Engineering and Environmental Challenges: Technical Symposium on Earth Systems Engineering - National Academy of Engineering (The National Academies Press, 2002)
Dealing with the challenges presented by climate change or rapid urban development require cooperation and expertise from engineering, social and natural sciences. Earth systems engineering is an emerging area of multidisclinary study that takes a holistic view of natural and human system interactions to better understand complex systems. It seeks to develop methods and tools that enable technically sound and ethically wise decisions. Engineering and Environmental Challenges presents the proceedings of a National Academy of Engineering public symposium on Earth systems engineering.
Keywords: Engineering and Technology

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2007 Symposium - National Academy of Engineering (The National Academies Press, 2008)
U.S. Frontiers of Engineering (USFOE) symposia bring together 100 outstanding engineers (ages 30 to 45) to exchange information about leading-edge technologies in a range of engineering fields. The 2007 symposium covered engineering trustworthy computer systems, control of protein conformations, biotechnology for fuels and chemicals, modulating and simulating human behavior, and safe water technologies. Papers in this volume describe leading-edge research on disparate tools in software security, decoding the "mechanome," corn-based materials, modeling human cultural behavior, water treatment by UV irradiation, and many other topics. A speech by dinner speaker Dr. Henrique (Rico) Malvar, managing director of Microsoft Research, is also included. Appendixes provide information about contributors, the symposium program, summaries of break-out sessions, and a list of participants. This is the thirteenth volume in the USFOE series.
Keywords: Engineering and Technology

Making a World of Difference: Engineering Ideas into Reality - National Academy of Engineering (The National Academies Press, 2014)
Fifty years ago, the National Academy of Engineering (NAE) was founded by the stroke of a pen when the National Academy of Sciences Council approved the NAE's articles of organization. Making a World of Difference commemorates the NAE anniversary with a collection of essays that highlight the prodigious changes in people's lives that have been created by engineering over the past half century and consider how the future will be similarly shaped. Over the past 50 years, engineering has transformed our lives literally every day, and it will continue to do so going forward, utilizing new capabilities, creating new applications, and providing ever-expanding services to people. The essays of Making a World of Difference discuss the seamless integration of engineering into both our society and our daily lives, and present a vision of what engineering may deliver in the next half century.
Keywords: Engineering and Technology

Livable Cities of the Future: Proceedings of a Symposium Honoring the Legacy of George Bugliarello - National Academy of Engineering (The National Academies Press, 2014)
At the beginning of the 20th century an estimated five percent of the world's population lived in cities. Today, half the world's population is urbanized. Urban sustainability is multifaceted and encompasses security, economics, environment and resources, health, and quality of life. It can be viewed as the intersection of two extremely complex and not yet fully understood processes, urbanization and global sustainability, which will increasingly overlap as urban populations continue to grow. Effective policies are critical for addressing urban sustainability, and must be politically realistic in deciding on appropriate balances, such as centralized versus decentralized systems, "soft" versus "hard" solutions, local versus regional focus, agriculture versus pollution, and free markets versus interventions. Livable Cities of the Future, a symposium honoring the legacy of George Bugliarello, was hosted October 26, 2012, by the Polytechnic Institute of New York University (NYU-Poly) in the Pfizer Auditorium of the Bern Dibner Library of Science and Technology. The event brought together more than 200 engineers, civic leaders, educators, and futurists to discuss how George Bugliarello's vision manifests itself in innovative urban planning for the cities of tomorrow. This report is a summary of the presentations and discussion at that event. The symposium objectives were to cultivate ideas for best practices and innovative strategies for sustainable urban development and to facilitate the evolution of New York City to a real-life laboratory for urban innovation. Participants heard the perspectives and experiences of representatives from private and public service operators, infrastructure agencies, and the academic community. Elected officials and other stakeholders in urban and other sectors examined issues critical to resilient and sustainable cities, such as energy, water supply and treatment, public health, security infrastructure, transportation, telecommunications, and environmental protection.
Keywords: Engineering and Technology

Engineering and the Advancement of Human Welfare: 10 Outstanding Achievements 1964-1989 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 1989)
This popularly written booklet contains nontechnical descriptions of 10 major engineering achievements selected by the National Academy of Engineering on the occasion of its 25th anniversary, December 5, 1989. The achievements are the moon landing, application satellites, the microprocessor, computer-aided design and manufacturing, computer-assisted tomography, advanced composite materials, the jumbo jet, lasers, fiber-optic communication, and genetically engineered products.
Keywords: Engineering and Technology

National Interests in an Age of Global Technology - National Academy of Engineering (The National Academies Press, 1991)
U.S. policymakers must come to terms with the implications of the "globalization of technology"—specifically, the dramatic increase in crossborder technical activities of private corporations and the rapid growth and redistribution of global technical capabilities since the mid-1970s. This book presents a policy framework for reconciling our national interests with the realities of the emerging global technical enterprise. Specific recommendations address how public policies can help ensure that U.S. citizens derive a fair share of the benefits of the global technology base. The volume discusses corporate nationality and its relevance to the policy debate, the need for greater international policy cooperation and negotiation in antitrust law, and the obligations of multinational corporations and their home and host governments. It also includes a series of detailed, up-to-date "technology profiles" of eight global industries, from aircraft engines to semiconductors.
Keywords: Engineering and Technology

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2015 Symposium - National Academy of Engineering (The National Academies Press, 2016)
This volume presents papers on the topics covered at the National Academy of Engineering's 2015 US Frontiers of Engineering Symposium. Every year the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and innovations in selected areas. The 2015 symposium was held September 9-11 at the Arnold and Mabel Beckman center in Irvine, California. The intent of this book is to highlight innovative developments in engineering research and technical work.
Keywords: Engineering and Technology

Managing Innovation: Cases from the Services Industries - National Academy of Engineering (The National Academies Press, 1988)
This book of case histories is devoted solely to service industries and the technologies that drive them, as told by those who have developed segments of these industries. The chapters cover innovations such as Federal Express's advanced system for package tracking, Citicorp's development of the Automated Teller Machine, AT&T's experience with mobile telephones, Bell & Howell's introduction of an automated automotive parts catalog, and the New York Stock Exchange's development of electronic trading. Some broader analyses discuss the interfaces between services technologies and manufacturing, operations research in services, and technology in professional services.
Keywords: Engineering and Technology